Περιγραφική μελέτη σύγκρισης του Κοινωνικού Κεφαλαίου στην Κύπρο μεταξύ διακριτών ομάδων του πληθυσμού – μητέρες, φροντιστές και νοσηλευτές - Χατζηττοφή, Ελένη (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2014)
Introduction: The concept of social capital consists of community network, participation in civic, access to institutional or informal information networks and information on reciprocity and trust and cooperation among people. Considered as a “public good”, social capital improves the environment and the health of the individual, family and community. The assessment and utilization will help the effective care in the community. In Cyprus, the social capital has been evaluated in three different studies using the scale of social capital in five distinct groups. Purpose: The quantitative assessment and comparison of social capital based on the Greek version of "Social Capital Questionnaire" in five distinct groups in Cyprus. Method: This is a descriptive comparison study with secondary analysis of data that have been collected within three research projects in Cyprus. The social groups represented in this study are nurses, caregivers of patients with dementia and mothers of children with cancer, with a total sample of 847 participants. For the data analysis used descriptive statistics, correlation analysis and exploratory factor analysis. Results: The results of the comparison between the groups showed that nurses have the highest degree of Social Capital, although the statistical difference is very small with limited statistical significance and appears to be primarily due to demographic characteristics. The results of the exploratory factor analysis of social capital for Cyprus recognized eight factors: “Participation in the local community, Family and friends connections, Neighborhood connections, Feelings of trust and safety, Proactivity in a social context, Tolerance of diversity, Value of life and Work connections”. The factors explaining 51% of variance. The measurement tool is reliable and valid. Conclusions: The observed differences between nurses and other groups of the population were due to demographic characteristics rather than “real” differences between the “property” they represent. A statistically significant relationship between social capital and demographic characteristics was acknowledged (gender, age, years of residence in the same direction, ownership and education).
Keywords: Social Capital; Social Capital Questionnaire; Κοινωνικό Κεφάλαιο; Κλίμακα Κοινωνικού Κεφαλαίου